The development of education in the era of the pandemic and in the perspective - Artemova, Evgeniya; Bodina, Elena; Antonova, Marina; Lukina, Elena; Jiang, Shangrong (Revista Conrado, 2022)
The article is devoted to two current trends in the development of modern education, which manifested themselves in the era of the pandemic and retain their importance in the short term – turbulence and unpredictability. The significance of turbulence in relation to the field of education, as well as in the context of the Fourth Industrial Revolution and the Sixth Technological Order, is considered. Comparative characteristics of mixed and hybrid learning formats are given. The consequences of using online and offline learning formats during the pandemic and after it are described. Conclusions are drawn about the need for critical rethinking and differentiated application of distance learning, as well as preventing the decline in the quality of liberal education. Keywords: Education, pandemic, digitalization, new normal, educational ecosystem. RESUMEN El artículo está dedicado a dos tendencias actuales en el desarrollo de la educación moderna, que se manifestaron en la era de la pandemia y conservan su importancia a corto plazo: la turbulencia y la imprevisibilidad. Se considera el significado de la turbulencia en relación al campo de la educación, así como en el contexto de la Cuarta Revolución Industrial y el Sexto Orden Tecnológico. Se dan características comparativas de formatos de aprendizaje mixtos e híbridos. Se describen las consecuencias del uso de formatos de aprendizaje en línea y fuera de línea durante la pandemia y después de ella. Se extraen conclusiones sobre la necesidad de un replanteamiento crítico y una aplicación diferenciada de la educación a distancia, así como evitar el deterioro de la calidad de la educación liberal. Palabras clave: Educación, pandemia, digitalización, nueva normalidad, ecosistema educativo.